Brine Shrimp Lethality, Aktivitas Antioksidan dan Kadar Total Fitokimia dari Ekstrak Etanol Kasumba Turate (Carthamus tinctorius) - Tahar, Nurshalati; Satrianegara, Fais; Rukmana, Rusmadi; Hamzah, Nursalam; Rukmana, Sitti; Alwi, Fitria; Roni, Abdul; Mukhriani, Mukhriani (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2023)
bstract: Kasumba turate had been used extensively in the treatment of varicella, but studies of safety, efficacy, and quality are incomplete. The objectives of these studies were to determine brine shrimp lethality, antioxidant activities and phytochemical contents of safflower ethanolic extract. The studies began with extraction, which soaked simplicia in 70% ethanol. Dried extract was determined for toxicity used brine shrimp lethality method. Although, antioxidant activities were measured by three methods, i.e., free radical scavenging (1,1-diphenyl-2-picrylhydrazil), cupric reducing antioxidant capacity, and ferric reducing antioxidant power. The phytochemicals total contents that measured were phenols, flavonoids and carotenoids. Based on studies result, rendemen extraction was 14.7%. The lethality level for brine shrimp was 109.64 ± 5.29 mg/L. The free radical scavenging, cupric reducing, and ferric reducing antioxidant activities were 35.40 ± 1.62 mg/L, 12.42 ± 0.95 mg/L and 36.47 ± 2.79 mg/L. Although, the phenol, flavonoid and carotenoid contents per gram were 135.40 ± 0.12 g gallic acid equivalent, 124.54 ± 3.38 mg quercetin equivalent and 27.25 ± 0.83 mg β-carotene equivalent. Based on these data, the ethanol extract of kasumba turate has high phytochemical and antioxidant potential and low toxicity.